2014
DOI: 10.3390/ijms150711234
|View full text |Cite
|
Sign up to set email alerts
|

Development of Laser Ionization Techniques for Evaluation of the Effect of Cancer Drugs Using Imaging Mass Spectrometry

Abstract: Recently, combined therapy using chemotherapy and photodynamic therapy (PDT) has been proposed as a means of improving treatment outcomes. In order to evaluate the efficacy of combined therapy, it is necessary to determine the distribution of the anticancer drug and the photosensitizer. We investigated the use of imaging mass spectrometry (IMS) to simultaneously observe the distributions of an anticancer drug and photosensitizer administered to cancer cells. In particular, we sought to increase the sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…There are numerous studies that explored the use of zeolites in medicine for imaging mass spectrometry, wound treatment, and drug delivery [ 32 , 33 , 34 , 35 , 36 ]. Zeolites are used as drug delivery systems for small molecules due to their unique porous characteristics and when the pore size can be matched to the size of drug molecules [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that explored the use of zeolites in medicine for imaging mass spectrometry, wound treatment, and drug delivery [ 32 , 33 , 34 , 35 , 36 ]. Zeolites are used as drug delivery systems for small molecules due to their unique porous characteristics and when the pore size can be matched to the size of drug molecules [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the signal intensity from a pure docetaxel sample at a concentration of 100 μM increased about 13-fold using a zeolite matrix with the droplet method. 13) In this study, we investigated two types of matrix application methods, the spray method and the droplet method. The matrix was sprayed using an airbrush (PS-153: 3500 PRO SPRAY Mk-2, Mr. Hobby, GSI Creos, Tokyo, Japan).…”
Section: Sample Preparationmentioning
confidence: 99%
“…. Graduate School of Engineering, Osaka University, Suita, Osaka, Japan 2. Graduate School of Science, Osaka University, Toyonaka, Osaka, Japan 3. Graduate School of Science and Engineering, Tokyo Metropolitan University, Hachioji, Tokyo, Japan 4.…”
mentioning
confidence: 99%
“…However, the detection sensitivity of IMS for drugs is lower than other drug imaging methods such as autoradiography, and some drugs could not effectively be ionized with MALDI. Therefore, a new ionization reagent, zeolite matrix, which is the mixture of zeolite and conventional MALDI matrix, has been developed to enhance the ionization efficiency of MALDI [1][2][3]. The detection sensitivity for an anticancer drug, docetaxel, was increased by 13-fold with the zeolite matrix [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation